2021
DOI: 10.3390/ph14080789
|View full text |Cite
|
Sign up to set email alerts
|

Selective DNA Gyrase Inhibitors: Multi-Target in Silico Profiling with 3D-Pharmacophores

Abstract: (1) Background: DNA gyrase is an important target for the development of novel antibiotics. Although ATP-competitive DNA gyrase (GyrB) inhibitors are a well-studied class of antibacterial agents, there is currently no representative used in therapy, largely due to unwanted off-target activities. Selectivity of GyrB inhibitors against closely related human ATP-binding enzymes should be evaluated early in development to avoid off-target binding to homologous binding domains. (2) Methods: To address this challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Representative compound 7l inhibited Hsp90-dependent luciferase refolding ( Supporting information, Figure S31 ), demonstrating that analogues of the virtual hit TVS-23 inhibit Hsp90. Next, we performed an in silico screening using a set of ligand-based pharmacophore models for the identification of Hsp90 NTD inhibitors [ 55 ], which resulted in no hits. Because the observed SAR is consistent with the hypothesis for the binding to the proposed Hsp90 CTD binding site and TVS-23 and its analogues do not have the necessary features of Hsp90 NTD inhibitors, we believe that they bind to the Hsp90 CTD.…”
Section: Resultsmentioning
confidence: 99%
“…Representative compound 7l inhibited Hsp90-dependent luciferase refolding ( Supporting information, Figure S31 ), demonstrating that analogues of the virtual hit TVS-23 inhibit Hsp90. Next, we performed an in silico screening using a set of ligand-based pharmacophore models for the identification of Hsp90 NTD inhibitors [ 55 ], which resulted in no hits. Because the observed SAR is consistent with the hypothesis for the binding to the proposed Hsp90 CTD binding site and TVS-23 and its analogues do not have the necessary features of Hsp90 NTD inhibitors, we believe that they bind to the Hsp90 CTD.…”
Section: Resultsmentioning
confidence: 99%
“…The best linear model's R correlation coefficient was 0.89 and 0.11 and resulted in the development of two nonlinear models [ 158 ]. In another study, Tomašič et al applied the three-dimensional pharmacophore profiling on selective DNA gyrase and HSP90 inhibitors [ 159 ]. The authors designed selective three-dimensional pharmacophore systems for GyrB, human topoisomerase II α (TopoII), and the HSP90 N-terminal domain (NTD) used as starting points for hit expansion and lead optimisation.…”
Section: Molecular Reactivity Allosteric Dynamics and Allosteric Designmentioning
confidence: 99%
“…In vitro studies against E. coli DNA gyrase and human TopoII validated the prediction of selective HSP90 NTD inhibition for 3 and 4, which was also confirmed in in vitro assays against E. coli DNA gyrase and human TopoII. It was confirmed that designing three-dimensional chemical parameter-based pharmacophore models are useful instruments for predicting the activity and selectivity of known and novel HSP90 and GyrB inhibitors [ 159 ].…”
Section: Molecular Reactivity Allosteric Dynamics and Allosteric Designmentioning
confidence: 99%
“…Similarly, many reported scaffolds with a urea moiety do act as potent DNA gyrase inhibitors embodied with antibacterial properties. 49–52 DNA gyrase is a type II topoisomerase that is a proven validated target in bacteria for the discovery of new antibacterial agents. 53…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, many reported scaffolds with a urea moiety do act as potent DNA gyrase inhibitors embodied with antibacterial properties. [49][50][51][52] DNA gyrase is a type II topoisomerase that is a proven validated target in bacteria for the discovery of new antibacterial agents. Considering the promising antimicrobial profile and the common target of the pyrazole scaffold and (thio)urea functionality, the present study aims to combine both moieties through molecular hybridization Fig.…”
Section: Introductionmentioning
confidence: 99%